Ethnopharmacology Study and Therapeutic Potential of Cassia alata for Skin Diseases - Vongphachanh Khampheng; Nanludet Phoummixay; Onmavong Sythanonxay (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study explores the ethnopharmacological knowledge of Cassia alata in the treatment of skin diseases in rural Laotian communities. Traditional practices highlight the use of the plant to treat fungal infections, eczema, and other skin conditions, driven by its antimicrobial and anti-inflammatory properties. This study aimed to document and scientifically validate the therapeutic applications of Cassia alata, with a focus on its safety, efficacy, and potential for dermatological product development. A mixed methods approach was used, involving ethnographic interviews with members of a rural Laotian community, laboratory tests to assess antimicrobial activity, and dermatological safety testing. The findings revealed that Cassia alata is widely used in rural areas, with a high degree of confidence in its ability to treat a variety of skin conditions. Microbiological tests confirmed its effectiveness against common pathogens such as Trichophyton and Candida, while dermatological tests demonstrated its safety with minimal side effects. The potential of the plant for dermatological product development is significant, with potential for commercialization and economic benefits to the local community. However, further research is needed to identify active compounds, assess long-term use, and optimize product formulations. This study provides a basis for future research on the global application of Cassia alata as a natural dermatological treatment.